Curricula for Sustainability in Higher Education - Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This books presents the curricula necessary for sustainability in higher education. It shows how the learning process is transforming in order to promote sustainability. It prepares administrators, teachers and students to diffuse the development in the field, showing a curricula based on three interconnected pillars: the environment, the economic and the social aspects. It contains 8 chapters introducing research advances in the field.
Keywords: Mechanical Engineering; Industrial management$1 (BEnvironmental aspects.s; Sustainability Management; Engineering/Technology Education